Policies and implementation of decent work in vocational education for persons with disabilities in Zhejiang Province in achieving common prosperity - Jia Qi; Xiao-Qiang Liu; Sheng Li (Jurnal Pendidikan Vokasi, 2024)
Decent work for persons with disabilities is a crucial aspect in enhancing skills, employability, and social inclusion. While developed countries have established comprehensive vocational training systems, limited research has explored how these initiatives are implemented in China at the provincial level. China’s 14th Five-Year Development Plan highlights vocational skill enhancement as a key strategy to protect labor rights for persons with disabilities. This study analyzes policies and strategic measures supporting decent work for persons with disabilities through vocational education in Zhejiang Province within the framework of common prosperity. Employing a qualitative descriptive analysis, the research reviews policy documents and existing vocational education practices. The findings reveal that the Zhejiang government has enacted multiple initiatives, including industry-based vocational training, digitalization of employment, and entrepreneurship support, to facilitate the integration of persons with disabilities into the workforce. Despite progress, challenges remain in enrollment, continuity of education, and resource availability. The study concludes that vocational education for persons with disabilities is not only a mechanism for skill enhancement but also a critical pillar in reducing socio-economic disparities. This research contributes both theoretically and practically by providing insights for policymakers and educators in developing inclusive employment policy models that can be adapted in other regions seeking to advance social equity and economic sustainability.